Music and dance of Bun That Luang and the standardisation of cultural memories in present Laos. - Jaehnichen, Gisa; Homsombat, Thongbang (Universiti Putra Malaysia Press, 2012)
Bun That Luang is one of the most important cultural events of the small inland country Laos. It is a traditional Buddhist festival as well as a demonstration of national culture. This paper aims to give an overview of its current organisation and of how music and dance performances are connected to the core activities of the traditional festival such as the circumambulation of the Golden Stupa (That Luang), processions of Buddhist and state hierarchy, offerings, and ritual field hockey. Due to the long term sharing of performance duties and having to consider the aesthetic values of certain state representatives, the variety of performances is becoming smaller each year. Modern media, on the other hand, distributes performances from Bun That Luang all over Laos which seem to equalise music and dance styles. These recent moves towards standardisation replace the notion of diversity in the cultural memory of Bun That Luang. The paper includes comprehensive audiovisual examples.